The Influence of Asset Management Information Systems, HR Competence, and Inventory Management Policies on The Management of State Property At The State Civil Servants Agency - Sibuea, Valen; Kantohe, Meidy (Abdurrauf Science and Society, 2025)
This study aims to examine the influence of the Asset Management Information System, HR Competence, and Inventory Management Policy on BMN Administration. This study was conducted at BKN. The data collection technique used a questionnaire distributed to 90 BKN employees with a total sample method with the criteria for selecting respondents, namely BMN management employees and inventory managers. The data analysis of this study used Partial Least Square (PLS) based on variants or components of the Structural Equation Modeling (SEM) approach and tested the influence of independent variables on the dependent variables. Data analysis used the SmartPLS application. The results of the study showed that the asset management information system had a positive and significant effect on the administration of state assets. HR competence and inventory management policies had a positive and moderate effect on the administration of state assets. The asset management information system, HR competence, and inventory management policies jointly influenced the administration of state assets at the State Civil Service Agency.